A machine learning approach on classifying orthopedic patients based on their biomechanical features - Hasan, Kamrul; Islam, Safkat; Samio, Md. Mehfil Rashid Khan (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.